1994
DOI: 10.1021/ac00090a019
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Organic Pollutants from Environmental Solids with Sub- and Supercritical Water

Abstract: Low-polarity organic pollutants such as polycyclic aromatic hydrocarbons (PAHs) typically have very low solubilities (e.g., ppb) in water at ambient conditions because of water's high polarity (dielectric constant, < = 80). However, the dielectric constant can be drastically lowered by raising the temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
280
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(293 citation statements)
references
References 23 publications
9
280
2
2
Order By: Relevance
“…Usually a small amount of modifier is considered as useful to significantly enhance the polarity of carbon dioxide. For example, 0.5 ml of Dichloromethane (CH 2 Cl 2 ) can enhance the extraction which is same for 4 h hydrodistillation (Hawthorne et al, 1994). The properties of sample and targeted compounds and the previous experimental result are main basis for selection of the best modifier.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…Usually a small amount of modifier is considered as useful to significantly enhance the polarity of carbon dioxide. For example, 0.5 ml of Dichloromethane (CH 2 Cl 2 ) can enhance the extraction which is same for 4 h hydrodistillation (Hawthorne et al, 1994). The properties of sample and targeted compounds and the previous experimental result are main basis for selection of the best modifier.…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%
“…The use of 100% water mobile phase has been recently studied by a number of researchers [19,21,54,55]. Smith et al [56], building on Hawthorne's [57] work using supercritical water, used subcritical (up to 2108C) water with no organic modifier to separate both polar and hydrophobic species including priority phenols and drugs on polymer reversed-phase (PRP) media. They showed that UV detection could be done even at very short wavelength (190 nm) and thus many species that do not absorb at longer wavelength can be easily detected.…”
Section: "Green" Htlcmentioning
confidence: 99%
“…In the mid 1990s Hawthorne proposed the use of superheated water as suitable solvent for the extraction of non-polar neutral compounds, such as PAHs, from environmental samples [1]. He demonstrated a dramatic 10 5 fold increase in the solubility of chrysene between room temperature and water at 225 °C [2].…”
Section: Superheated Water As a Solvent For Extractionmentioning
confidence: 99%